The patient knows best: significant change in the physical component of the Multiple Sclerosis Impact Scale (MSIS‐29 physical) - Costelloe, Lisa (BMJ Group, 2007)
AIM: The aims of this study were to determine the reliability, responsiveness and minimally important change score of the Multiple Sclerosis Impact Scale (MSIS)‐29 physical using the Expanded Disability Status Scale (EDSS) as an anchor measure. METHODS: 214 patients with multiple sclerosis (MS) (EDSS 0–8.5) had concurrent MSIS‐29 and EDSS assessments at baseline and at up to 4 years of follow‐up. RESULTS: 116 patients had unchanged EDSS scores. Stability of the MSIS‐29 physical (mean change 0.1 points) was better in the 85 patients with EDSS 0–5.0 than in the 31 patients with EDSS 5.5–8.5 in whom the MSIS‐29 physical score fell by 8 points, a response shift phenomenon. A floor effect for the MSIS‐29 was observed in 5% of stable patients at both time points. 98 patients experienced EDSS change with moderately strong statistically significant correlations between change scores in the EDSS and the MSIS‐29 physical (r = 0.523, p<0.0001). Effect sizes for MSIS‐29 physical change were moderate to large. Using receiver operating characteristic curves, the MSIS‐29 change score which produced a combination of optimal sensitivity and specificity was chosen for both EDSS ranges. For EDSS range 5.5–8, a change score of 8 had a sensitivity of 87% and specificity of 67%. For EDSS 0–5.0, a change score of 7 had a sensitivity of 78% and a specificity of 51%. CONCLUSIONS: The MSIS‐29 physical performs well over time, and is suitable for use in trials; a minimal change score of 8 points in the MSIS‐29 is clinically significant.